Gold(I)-catalyzed hydroindolylation of allenyl ethers - Kona, Chandrababu Naidu; Shinde, Mahesh H.; Ramana, Chepuri V. (Organic & Biomolecular Chemistry, 2015)
The gold(I)-catalyzed reaction/rearrangement of allenyl ethers has been investigated in the presence of indoles. Either hydroindolylation or alkylation of an indole with the pendant group of allenyl ether has been observed. The reaction outcome seems to be decided mainly by the nature of the pendant group of the allenyl ether. Control experiments are indicative of an inner sphere mechanism for the hydroindolylation reaction.

Apparent umpolung reactivity of indole through [Au]-catalysed cyclisation and lewis-acid-mediated allylation - Shinde, Mahesh H.; Ramana, Chepuri V. (Chemistry-A European Journal, 2020)
The sequential functionalization of indole C2 and C3 in an umpolung fashion was executed with a predesigned substrate and choice of reagents. The developed method comprises gold-catalysed alkynol cycloisomerisation/intramolecular addition of C2 of indole and subsequent BF3.OEt2-mediated regioselective C3 allylation, resulting in the synthesis of the functionalized indoloisoquinolinone scaffold. The reaction involves 5-endo-alkynol cycloisomerisation and the dearomative addition of indole C2 to the intermediate oxocarbenium cation, which results in two equilibrating fused and spiropentacyclic intermediates, which upon treatment with allyl silane in the presence of BF3.OEt2, undergo selective indole C3 allylation. Other nucleophiles, such as hydride, azide and indole, were also found to be compatible with this process.
Keywords: Allylation; cyclization; domino reactions; Gold; umpolung

Ru-catalyzed asymmetric transfer hydrogenation of alpha-acyl butyrolactone via dynamic kinetic resolution: asymmetric synthesis of bis-THF alcohol intermediate of darunavir - More, V. Ganesh; Malekar, V. Pushpa; Kalshetti, Rupali G.; Shinde, Mahesh H.; Ramana, V. Chepuri (Tetrahedron Letters, 2021)
The Ru-catalyzed enantio- and diastereoselective dynamic kinetic resolution of alpha-(benzyloxy/benzoyloxy)acyl-gamma-butyrolactones has been examined via transfer hydrogenation. Employing the in situ prepared (R,R)-Ru-FsDPEN catalyst, the transfer hydrogenation of using formic acid/triethylamine at rt gave the corresponding (S)-3-((S)-2-(benzyloxy/benzoyloxy)-1-hydroxyethyl)dihydrofuran-2(3H)-on e with good to excellent diastereo- and enantioselectivity. One of the resulting hydrogenation product prepared on gram scales was utilized for the synthesis of (3R,3aS,6aR)-hexahydrofuro[2,3-b]furan-3-ol (1), a key synthetic intermediate of various HIV protease inhibitors such as darunavir with excellent enantio-(95% ee) and diastereoselectivities (dr 95:5). (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: Bis-THF-OH intermediate; Darunavir; Dynamic kinetic resolution; Ru-catalysis; transfer hydrogenation

Facile synthesis of the spiro-pyridoindolone scaffold via a gold-catalysed intramolecular alkynol cyclisation/hydroindolylation - Shinde, Mahesh H.; Ramana, V. Chepuri (Organic & Biomolecular Chemistry, 2022)
A simple approach for the synthesis of pyridoindolone scaffolds with a spiroannulated tetrahydrofuran ring is described. The overall process comprises intramolecular sequential gold-catalysed 5-endo-dig alkynol cycloisomerization and subsequent addition of indole C2 to the in situ generated oxocarbenium cation.

Synthesis of central spiro-bis-THF fragments of symbiospirols A-C - Shinde, Mahesh H.; Kona, Chandrababu N.; Ramana, V. Chepuri (New Journal of Chemistry, 2022)
The gold catalysed alkynediol spiroketalization to assemble the central spiro-bis-THF fragments (C22-C33 and C36-C47) of symbiospirols A-C is documented. The adopted chiral pool approach employed commercially available d-glucose and l-malic acid in the synthesis of key building blocks. In addition, two other possible diastereomers have been synthesized in order to establish the relative stereochemistry of the unassigned THF-center of symbiospirols B/C.